Job satisfaction factors and job performance among Petronas NGV staff / Mohamed Nabiil Ashaaree - Ashaaree, Mohamed Nabiil (Faculty of Business and Management, 2019)
Job satisfaction and job performance are two important elements needed in establishing an organization in the industry. Past studies have shown that employee’s satisfaction towards the work will enhance and improve the organization and employee performance which will boost on the organization’s profitability. In this modern and diverging market condition, every organization focuses on achieving good satisfaction level among its employee to boost the productivity and profitability of the organization. In this study, the research will be on the how job satisfaction factors contribute towards the job performance among PETRONAS NGV staff. The independent variables that will be tested are workplace environment, employee empowerment and salary. The questionnaire have been distributed among the PETRONAS NGV staff and the data were analysed and shared at the end of this study.